Satellite depiction of the evolution of a West African squall cluster - Fernández Rojas, Walter (1989)
West African squall lines or disturbance lines have been studied by several investigators (e.g., Hamilton and Archbold 1945; Eldridge 1957; Fortune 1980; Fernandez 1982a, 1982b) and their climatological aspects are, in general, well known (Aspliden et al. 1976). The squall line is found to be the leading portion of a propagating disturbance, namely the squall cluster, which consists of the squall line (a line of cumulonimbus clouds) and the cloud shield (anvil cloud) that trails behind it. This paper uses METEOSAT imagery to investigate the evolution of an unusually persistent squall cluster.